How to recognize silent atrial fibrillation in pacemakers and defibrillators—the value of atrial electrograms - Benezet-Mazuecos, Juan (J Thorac Dis, 2018)
Today’s pacemakers and defibrillators include diagnostic tools for detecting and treating cardiac arrhythmias like silent atrial fibrillation as atrial high rate episodes (AHREs). This diagnostic capability is crucial to prevent the potential embolic complications this AHREs are related to. However, sometimes data retrieved from diagnostic counters may be misleading reflecting limitations of detection algorithms, which must follow mathematical rules to classify events on a beat-to-beat basis. The incorporation of stored electrograms has been an important milestone in improving the diagnostic capabilities of these devices confirming the arrhythmia diagnosis.